2021
DOI: 10.15381/rivep.v32i5.21341
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico post mortem de Fasciola hepatica en bovinos faenados en la planta de beneficio de Sogamoso (Boyacá, Colombia)

Abstract: El objetivo del estudio fue determinar la prevalencia de distomatosis hepática en bovinos faenados en la planta de beneficio de Sogamoso (Boyacá, Colombia), y definir la técnica diagnóstica más efectiva para establecer la presencia del parásito. Se estableció un tamaño muestral de 343 individuos teniendo en cuenta la tasa de sacrificio mensual de la planta. Se tomaron muestras de heces, sangre y contenido biliar y se colectaron los parásitos adultos del ducto biliar. En el examen coproparasitológico se utilizó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Regarding the sex of the evaluated animals, studies have reported a greater prevalence of the disease in female animals [14,30,37], which is consistent with data found in San Miguel de Sema and Ubaté. However, Ortiz-Pineda et al [13] reported that male animals showed greater seroprevalence, consistent with data found in Chiquinquirá. Furthermore, a statistically significant association was found between the sex of the cattle and the presence of antibodies against fasciolosis in Ubaté, which is in agreement with data reported by Chaouadi et al [37], Pinilla et al [14], and Utrera-Quintana et al [8], where female animals presented a higher risk of parasitic infection, establishing the female sex as a risk factor for the disease.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Regarding the sex of the evaluated animals, studies have reported a greater prevalence of the disease in female animals [14,30,37], which is consistent with data found in San Miguel de Sema and Ubaté. However, Ortiz-Pineda et al [13] reported that male animals showed greater seroprevalence, consistent with data found in Chiquinquirá. Furthermore, a statistically significant association was found between the sex of the cattle and the presence of antibodies against fasciolosis in Ubaté, which is in agreement with data reported by Chaouadi et al [37], Pinilla et al [14], and Utrera-Quintana et al [8], where female animals presented a higher risk of parasitic infection, establishing the female sex as a risk factor for the disease.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, at the national level, the presence of antibodies was established in 5.6% of cattle evaluated in Sabana de Torres (Santander) [34]; 52.4% in animals from the municipalities of El Encino, Duitama, and Belén [35]; 37.8% in 16 municipalities in Colombia [14]; and 13.7% in cattle slaughtered at the Sogamoso (Boyacá) processing plant [13]; these rates were lower than those found in Chiquinquirá, Ubaté, and San Miguel de Sema. The different seroprevalence rates found in our study may be due to the number of bovines sampled, the type of study performed, the ELISA kit used, and the environmental conditions of the geographical location where the study was conducted, because it has been reported that the infection involves a suitable intermediate host in appropriate environments, such as proximity to streams and springs, an optimal temperature between 10°C and 25°C, and sufficient humidity for the disease to occur in ruminants [32,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parasite is endemic in four recognized regions: Nariño, Cundiboyacense highlands, Santander, Norte de Santander highlands, and highlands of the west of Antioquia (19). The prevalence of F. hepatica varies across these areas, with values ranging from 9.5 to 30.9% (20)(21)(22)(23)(24)(25). However, knowledge of the parasite's genetic diversity and intrapopulation structure in the country is limited.…”
Section: Introductionmentioning
confidence: 99%